Interpreting qualitative data methods for analyzing talk, text and interaction - Silverman, David 1943- (London SAGE Publications, Ltd, 2006)
This text offers practical and sensible advice on the central issues involved in qualitative research, from one of the leading researchers. The book assesses an unrivalled range of qualitative methods, and the strengths of methodologies.
Theory and method in qualitative research -- Beginning research -- What is qualitative research? -- Methods -- Ethnography and observation -- Interviews -- Texts -- Naturally occurring talk -- Visual images -- Research practice -- Credible qualitative research -- Research ethics -- Writing your report -- Implications -- The relevance of qualitative research -- The potential of qualitative research : eight reminders -- Appendix: Simplified transcription symbols.
Includes bibliographical references (pages [406]-421) and indexes.
Keywords: Sociology -- Research; Sociology -- Methodology; Social sciences -- Research; Discourse analysis